Assessment Of Knowledge And Evaluation Of Tuberculosis Treatment Outcomes Among General And Diseased Populations In North East Libya - Solliman, Mukhtar A. Muftah (2012)
Tuberculosis (TB) still remains a leading cause of adult mortality and morbidity with an estimated 9 million new cases detected around the globe annually. Libya has faced gradual increase in the prevalence of TB from 2000 to 2006 and this had posed considerable challenges for the healthcare providers to manage TB timely and effectively. Within this context, assessment of TB related knowledge among general and diseased population is necessary in order to plan effective public health curative and preventive programs.